"I will get this degree" : an exploration of the motivations and coping skills of mature female postgraduate psychology graduates. - De Freitas, M. S. (My University, 2013)
This research study explored the dimensions of motivation that may exist for mature psychology graduates when completing their postgraduate degree. And because it is widely acknowledged that stress is often a close companion to motivation, specifically in the pursuit of academic goals, the study also investigated those aspects of coping skills these individuals employed to sustain their motivation in completing their studies. Eight mature female psychology postgraduates from four different South African public universities were identified using a non probability sampling technique. Semi structured interviews were then carried out with the eight participants; the interviews were then transcribed and analysed using content analysis. The results of the study indicated that self efficacy; intrinsic motivation, attribution and achievement goals all play a role in the students’ motivation. It further indentified perseverance as an important factor in the students’ completion of their studies. Positive beliefs, problem solving strategies and social support appeared to be the most widely used coping skills by this sample.
Keywords: Psychology--Study and teaching (Higher)--South Africa.; Women graduate students--South Africa.; Motivation in adult education--South Africa.